TThe problem of justice in the context of value contradictions in modern society (Journal of Philosophy Culture and Political Science, 2026)
In their article, the authors examine the problem of justice as a fundamental principle of social order in the context of conflicting values of modern society. The study's relevance lies in the growing polarization of values worldwide, which directly impacts the formation of public institutions and hinders societal harmony. In today's world, conflicts between different social groups often arise due to differences in the interpretation of justice, which is exacerbated by factors such as economic inequality, cultural and religious diversity, and rapid technological development. This creates additional challenges for societies seeking integration and stability. The article's purpose is to analyse approaches to the conceptualisation of justice in modern conditions and identify ways to achieve it, taking into account value pluralism. To achieve this goal, the authors employed an interdisciplinary approach, incorporating methods of analysis, synthesis, and comparative research, drawing on the work of classical philosophers and contemporary researchers in the field of justice theory. The study's results suggest that the issue of justice is closely tied to striking a balance between individual rights and collective interests, while also taking into account cultural and ideological diversity. The author proposes a conceptual model that enables consideration of different perspectives in decision-making within public institutions. In their conclusions, the authors substantiate the need for an integrative approach to addressing the issue of justice, based on the principles of dialogue, mutual respect, and compromise. In the future, this may help reduce societal tensions and create conditions for sustainable development.Keywords: justice, social harmony, ethical principles, modern values, sustainable development, globalisation